The effect of using ‘displacement’ to encourage the movement of water voles Arvicola amphibius in lowland England - Gelling, M; Harrington, A; Dean, M; Haddy, E; Marshall, C; Macdonald, D (University of Cambridge, 2018)
Water voles are nationally protected as one of Britain’s most endangered wild mammals. However conflict can arise where works are required along short sections of riverbank. Vegetation removal is commonly used with the aim of displacing water voles towards safety prior to development, despite a lack of evidence demonstrating its efficacy. This study aimed to investigate the movement and fate of water voles in response to vegetation removal, by radio-tracking individuals during spring and autumn at 12 experimental and four control sites. Vegetation was removed to ground level from 50 m of riverbank at experimental sites, and observed home ranges were compared before and after vegetation removal. There was no significant net movement of water voles out of areas where vegetation had been removed in either spring or autumn, although movement of individuals both in and out of the works area did occur. There was no impact of treatment on water vole survival in either season.